2009
DOI: 10.1073/pnas.0902232106
|View full text |Cite
|
Sign up to set email alerts
|

Association of survival and disease progression with chromosomal instability: A genomic exploration of colorectal cancer

Abstract: During disease progression the cells that comprise solid malignancies undergo significant changes in gene copy number and chromosome structure. Colorectal cancer provides an excellent model to study this process. To indentify and characterize chromosomal abnormalities in colorectal cancer, we performed a statistical analysis of 299 expression and 130 SNP arrays profiled at different stages of the disease, including normal tissue, adenoma, stages 1-4 adenocarcinoma, and metastasis. We identified broad (> 1/2 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
298
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(325 citation statements)
references
References 37 publications
25
298
1
1
Order By: Relevance
“…Along with losses in 14q, 17p, and 15q, these are the most commonly occurring chromosomal aberrations in CRCs. [22][23][24][25] In contrast, a typical MIN tumor (sample C0323A; Figure 1C is devoid of these chromosomal aberrations and remains diploid. Of all of the common somatic copy number changes in CRCs, it is the loss of 18q 24,26 -39 that is most clearly associated with poor prognosis (Table 1).…”
Section: Somatic Copy Number Aberrations In Crcsmentioning
confidence: 92%
See 1 more Smart Citation
“…Along with losses in 14q, 17p, and 15q, these are the most commonly occurring chromosomal aberrations in CRCs. [22][23][24][25] In contrast, a typical MIN tumor (sample C0323A; Figure 1C is devoid of these chromosomal aberrations and remains diploid. Of all of the common somatic copy number changes in CRCs, it is the loss of 18q 24,26 -39 that is most clearly associated with poor prognosis (Table 1).…”
Section: Somatic Copy Number Aberrations In Crcsmentioning
confidence: 92%
“…Both these genes are often up-regulated in CRCs. [45][46][47] The 13q and 20q chromosomal arms, both of which harbor a great percentage of genes with up-regulated expression, 24,25 are also often gained in CRCs. In our CRC genome-wide expression analysis, one of the 13q genes that turned out to be very highly up-regulated was CUL4A, which has also been found to be copy number-dysregulated (ie, amplified in both copy number and expression) in breast cancer.…”
Section: Dysregulation Of Genes In Regions Of Chromosomal Gainmentioning
confidence: 99%
“…In addition, we tested the effect of CDK8 reduction on cell cycle distribution by flow cytometry analyses, and we observed that knockdown of CDK8 evidence that links dysregulated CDK8 to a variety of human cancers in recent years. 17 For example, CDK8 gene is amplified or overexpressed in colorectal and gastric cancers, 6,[17][18][19][20][21][22][23] and overexpression of wild-type CDK8 in untransformed 3T3 cells led to anchorage-independent growth. 6 In addition, loss of the histone variant macroH2A increases the expression of CDK8 in melanoma.…”
Section: Tumor-suppressive Effects Of Cdk8 In Endometrial Cancer Cellsmentioning
confidence: 99%
“…The clinical relevance of these alterations is highlighted by their association to metastatic progression and poor prognosis in CRC patients (Sheffer et al 2009;Loo et al 2013). Structural and functional interrogations of these regions have described putative oncogenes at chromosomes Ó 2014 Adler et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml).…”
mentioning
confidence: 99%